A Stable Layered Oxide Cathode Material for High‐Performance Sodium‐Ion Battery. Issue 19 (27th March 2019) - Xiao, Yao; Zhu, Yan‐Fang; Yao, Hu‐Rong; Wang, Peng‐Fei; Zhang, Xu‐Dong; Li, Hongliang; Yang, Xinan; Gu, Lin; Li, Yong‐Chun; Wang, Tao; Yin, Ya‐Xia; Guo, Xiao‐Dong; et al.
Abstract: As one of the most promising cathode candidates for room‐temperature sodium‐ion batteries (SIBs), P2‐type layered oxides face the challenge of simultaneously realizing high‐rate performance while achieving long cycle life. Here, a stable Na2/3 Ni1/6 Mn2/3 Cu1/9 Mg1/18 O2 cathode material is proposed that consists of multiple‐layer oriented stacking nanoflakes, in which the nickel sites are partially substituted by copper and magnesium, a characteristic of the material that is confirmed by multiscale scanning transmission electron microscopy and electron energy loss spectroscopy techniques. Owing to the optimal morphology structure modulation and chemical element substitution strategy, the electrode displays remarkable rate performance (73% capacity retention at 30C compared to 0.5C) and outstanding cycling stability in Na half‐cell system couple with unprecedented full battery performance. The underlying thermal stability, phase stability, and Na + storage mechanisms are clearly elucidated through the systematical characterizations of electrochemical behaviors, in situ X‐ray diffraction at different temperatures, and operando X‐ray diffraction upon Na + deintercalation/intercalation. Surprisingly, a quasi‐solid‐solution reaction is switched to an absolute solid‐solution reaction and a capacitive Na + storage mechanism is demonstrated via quantitative electrochemical kinetics calculation during charge/discharge process. Such a simple and effective strategy might reveal a new avenue into the rational design of excellent rate capability and long cycle stability cathode materials for practical SIBs. Abstract : A stable copper and magnesium cosubstituted Na2/3 Ni1/6 Mn2/3 Cu1/9 Mg1/18 O2 cathode material consisting of multiple‐layer oriented stacking nanoflakes is reported. An optimal structure design and a chemical element substitution strategy are demonstrated to greatly improve Na + transport kinetics and structural stability of P2‐type cathode material, resulting in high‐rate and long cycle life for a sodium‐ion battery.